The Effect of Work Discipline and Workload on Employee Performance - Masruddin, Nur Pita Devi; Saharuddin, S.; Hasbi, Andi Rizkiyah (Manunggal Halim Jaya, 2026)
This study evaluates how work discipline and workload affect employee performance at CV. Karya Tani Kamanre. This study focuses on the importance of organizational success in managing adequate human resources to improve organizational performance, with work discipline and workload as the main factors. This study uses a quantitative approach, where data is obtained through observation and questionnaires distributed to 30 employees using saturated sampling techniques. The results of this study indicate that the work discipline variable (X1) has a positive and significant effect on employee performance (Y). This indicates that high work discipline can improve employee performance. Workload (X2) negatively and significantly affects employee performance (Y). This indicates that an increase in the workload given to employees can decrease employee performance. Work discipline (X1) and workload (X2) have a simultaneous effect on employee performance (Y). This result indicates that both factors contribute to influencing employee performance. Therefore, H3 is accepted. This finding indicates that discipline at work is essential to improve employee performance.